Boundary elements for joule heating of solids with orthotropic conductivities - Meric, RA (Elsevier BV, 1997)
A quasi-coupled problem of joule heating in solids has been investigated using the boundary element method. An electric potential field satisfying Poisson's equation is first solved within the medium. Internal fluxes of the potential generate an electrically induced heat source. Another Poisson's equation representing the heat conduction phenomenon is next solved using the same numerical method. The electrical and thermal conductivities are taken as orthotropic without any space dependency. After verifying the present computer code, four example problems with various conductivities have been analyzed by the proposed solution technique.